Analisis perbandingan perencanaan strategis pada Bank Umum (Persero) di Indonesia - Angelica, Zahwa; Cecilia, Putri Engellina; Vinori, Jafria (Maliki Interdisciplinary Journal, 2023)
With the increasing growth of similar companies, competition becomes an aspect that cannot be avoided. To face this competition, a company needs to carry out a thorough analysis of the internal situation of the company and also the external environment in which the company will compete. From the understanding gained through this analysis, the company can then determine the strategic direction it should take for the future. The purpose of this writing is to compare strategic planning at Bank Umuru (Persero). The three banks focus on improving digital services and operational efficiency, but with different strategies according to their respective segmentation and position in the banking industry.